Detection and Analysis of Burned Areas with Sentinel-2 MSI and Landsat-8 OLI: Çanakkale / Gelibolu Forest Fire - Beyza Yılmaz; Mehveş Demirel; Filiz Bektaş Balçık (Doğal Afetler ve Çevre Dergisi)
Recently, increasing wildfires have caused severe damage to vegetation and many living creatures. Remote sensing technologies and various algorithms are used to determine and analyze the burned forest areas. Different remotely sensed images such as Sentinel-2 MSI, Landsat, MODIS, SPOT were used to determine forest fire damage and to produce maps for burned areas. In this study, the 6 July 2020 dated wildfire that occurred in the Gallipoli district of Çanakkale province has been analyzed by using Sentinel-2 MSI and Landsat-8 OLI satellite images. Burned Area Index (BAI), Normalized Moisture Index (NDMI), Normalized Burn Ratio (NBR), and Normalized Difference Vegetation Index (NDVI) were calculated with the pre and post-fire satellite images of the study area. The differences of the pre and post-fire indices were calculated to determine the burned forest area. Error matrix was produced for accuracy assessment. Overall accuracy, user accuracy, producer accuracy, and Kappa statistics were calculated, and performances were evaluated for different sensors and different indices by comparing the accuracy assessment results. The highest accuracy results were achieved with Differenced Normalized Difference Vegetation Index (dNDVI) for both Landsat-8 OLI and Sentinel-2 MSI images, and Kappa statistic results were obtained as 0.94 and 0.95, respectively.